Documentary Film Production as a Promotional Medium in Nagari Pasilihan, Solok Regency. - Fadilla, Siti; Rikarno, Riki; Marhen, Marhen; Ilham, Afdi Nur; Hulum, Fuadil (ARTCHIVE: Indonesian Journal of Visual Arts and Design, 2024)
Indonesia has a wealth of diverse cultural heritage, which is spread from sabang to merouke. One of them is the culture in Nagari Pasilihan, Solok Regency. Nagari Pasilihan is one of the Nagari that has natural resources that produce wealth to be able to promote its territory to the rest of the world. This article aims to discuss how natural resources through documentary film production. This documentary film production is based on the theory of film, documentary film, cinematography, and editing. Data collection was carried out using observation, documentation and interview methods. The data collection technique is done by analyzing and presenting it in a documentary film. This article produces a documentary film with a duration of 12 minutes that reveals the essence of natural resources so as to promote Nagari Pasilihan, Solok Regency.